The use of remote sensing technologies in the design of maps of agricultural land - Ganiyev Yunusali Yusufovich; Yokubov Sherzodbek Shavkat ogli (Zien Journals, 2023)
This article provides information on the use of remote sensing technologies in the design of agricultural land maps, the purposes of remote sensing mapping, the methods of mapping in remote sensing and area monitoring
Keywords: remote sensing; map; aerial photography